Cerebral aspergillosis due to Aspergillus fumigatus in AIDS patient: first culture - proven case reported in Brazil - Vidal, José E. (2005)
Cerebral aspergillosis is a rare cause of brain expansive lesion in AIDS patients. We report the first culture-proven case of brain abscess due to Aspergillus fumigatus in a Brazilian AIDS patient. The patient, a 26 year-old male with human immunodeficiency virus (HIV) infection and history of pulmonary tuberculosis and cerebral toxoplasmosis, had fever, cough, dyspnea, and two episodes of seizures. The brain computerized tomography (CT) showed a bi-parietal and parasagittal hypodense lesion with peripheral enhancement, and significant mass effect. There was started anti-Toxoplasma treatment. Three weeks later, the patient presented mental confusion, and a new brain CT evidenced increase in the lesion. He underwent brain biopsy, draining 10 mL of purulent material. The direct mycological examination revealed septated and hyaline hyphae. There was started amphotericin B deoxycholate. The culture of the material demonstrated presence of the Aspergillus fumigatus. The following two months, the patient was submitted to three surgeries, with insertion of drainage catheter and administration of amphotericin B intralesional. Three months after hospital admission, his neurological condition suffered discrete changes. However, he died due to intrahospital pneumonia. Brain abscess caused by Aspergillus fumigatus must be considered in the differential diagnosis of the brain expansive lesions in AIDS patients in Brazil.